(3GdOQQ GdeQUYI HCNHGQ CYjGf OQYIs - (3GHf fGUQ GdOQYj , eMeO Hf eMeO Hf CMeO Hf fGUQ, CHh YHO Gddg,J (B1085 (3g` s
(3ChdgG (B:s
(3hHYO , adeG cGf Yde GdJGQjN eJCcOI Ydi cd faS RcjI cfJ eef CYJfi HeWGdYI cJH GdCNHGQ NUhUkG (B[(3dCgd(B] (3HdOfG GdCQHYjf s
(3BNQgG (B:s
(3hbGd BNQ CQLhYah QHj djQTOfj Edi MSf GdNJGe hcGf GdaQGZ ef JYdjbg SfI EKfJjf hNeSjf heGFI hCda HGdRGhjI GdfGUQjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B187s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B687 ; (3Odjd eDQN GdeZQH (B- (3GdLRA (B2 - (3U (B687 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3c (B265) s
Keywords: (3GdJGQjNs